2012
DOI: 10.1074/jbc.m111.331553
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues That Underpin Interactions within the Eukaryotic Initiation Factor (eIF2) 2B Complex

Abstract: Background: eIF2B is a multisubunit protein that regulates protein synthesis. Results: We identify conserved residues in eIF2B␥ and eIF2B⑀ that are involved in interactions between subunits of the eIF2B complex. Conclusion: Highly conserved regions and residues in eIF2B are crucial for creating eIF2B protein complexes. Significance: This study provides new insights into the interactions that hold together the eIF2B holocomplex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…Plasmids encoding N‐terminal myc‐tagged eIF2B subunits and His 6 /Myc‐tagged eIF2Bε and eIF2B δ are described elsewhere (9, 15). His 6 /myc‐tagged eIF2Bα was produced by cloning the coding ORF of eIF2Bα into the pHM backbone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids encoding N‐terminal myc‐tagged eIF2B subunits and His 6 /Myc‐tagged eIF2Bε and eIF2B δ are described elsewhere (9, 15). His 6 /myc‐tagged eIF2Bα was produced by cloning the coding ORF of eIF2Bα into the pHM backbone.…”
Section: Methodsmentioning
confidence: 99%
“…The N‐terminal part of eIF2Bε shows sequence similarity to eIF2Bγ (7, 8). We recently showed that highly conserved residues within the regions of human eIF2Bγ and ‐ε are crucial for their mutual interaction (9). eIF2Bα, β, and δ also show mutual sequence similarity (10); in yeast, they form a stable heterotrimeric subcomplex (11).…”
mentioning
confidence: 99%
“…These molecules have been termed alarmins or danger-associated molecular patterns, and include High Mobility Group Box 1 (HMGB1), uric acid, ATP, heat shock proteins, DNA, IL-1α, and filamentous actin (Rock et al, 2010; Ahrens et al, 2012; Zhang et al, 2012). Several recent studies have suggested that uric acid, DNA, ATP, and HSP70 are involved in the immunostimulation by aluminum adjuvants (Kool et al, 2008b; Marichal et al, 2011; Riteau et al, 2012; Wang et al, 2012). Intraperitoneal injection of aluminum-containing adjuvant induced an increase of uric acid, and treatment of mice with uricase decreased activation of antigen-specific T cells in the draining lymph node suggesting a role for uric acid in the activation of the immune response by aluminum-containing adjuvants (Kool et al, 2008b).…”
Section: Aluminum Adjuvants and Dendritic Cellsmentioning
confidence: 99%
“…Injection of IRF3-deficient mice with aluminum adjuvant induced similar accumulation of inflammatory cells in the peritoneal cavity and OVA-specific IgG1 as wild-type mice, but IRF3-deficiency abolished the OVA-specific IgE response (Marichal et al, 2011), suggesting a dissociation of the IgG1 and IgE response. Subcutaneous injection of aluminum-adjuvanted-OVA induced increased expression of membrane HSP70 in splenic dendritic cells (Wang et al, 2012). A similar effect was seen upon administration of OVA with known stress-inducing compounds.…”
Section: Aluminum Adjuvants and Dendritic Cellsmentioning
confidence: 99%
“…Furthermore, by inactivating CHIP via deubiquitination, ataxin-3 tightly regulate the activity of CHIP within the protein quality control pathway, ensuring that it can only ubiquitinate misfolded proteins targeted for degradation. However, if CHIP is unable to remove these proteins, resulting in an accumulation of misfolded proteins, ataxin-3 again utilizes its editing activity to help sequester these proteins into structures termed aggresomes, thereby mitigating the effects of misfolded protein toxicity within the cell (Ouyang et al, 2012; Wang et al, 2012). In this pathway, ataxin-3 edits Ub conjugates on misfolded proteins to generate free Ub C termini that are recognized by HDAC6 and subsequently sequestrated to the aggresomes (Ouyang et al, 2012).…”
Section: Ataxin-3 and Chipmentioning
confidence: 99%